Three Unresolved Issues in Human Morality. (May 2018) - Kagan, Jerome
This article discusses three major, but related, controversies surrounding the idea of morality. Is the complete pattern of features defining human morality unique to this species? How context dependent are moral beliefs and the emotions that often follow a violation of a moral standard? What developmental sequence establishes a moral code? This essay suggests that human morality rests on a combination of cognitive and emotional processes that are missing from the repertoires of other species. Second, the moral evaluation of every behavior, whether by self or others, depends on the agent, the action, the target of the behavior, and the context. The ontogeny of morality, which begins with processes that apes possess but adds language, inference, shame, and guilt, implies that humans are capable of experiencing blends of thoughts and feelings for which no semantic term exists. As a result, conclusions about a person's moral emotions based only on questionnaires or interviews are limited to this evidence.